Negotiating with backbone : eight sales strategies to defend your price and value - Holden, Reed K. (FT Press, 2012)
Sales professionals now confront the most serious threat to their success. Regardless of their size, industry, country, customer type, nature of the relationship or amount of value they provide, sales professionals are finding that purchasing decisions are increasingly being limited by procurement. The modern procurement function is purchasing on steroids. Where traditional purchasing managers negotiated, procurement officials attempt to dictate. Procurement deploys a variety of tactics designed to do one thing: gain unprecedented discounts and concessions out of even the most sophisticated sales professionals. This book is a strategy guide for salespeople to help them level the procurement playing field by showing readers how to assess the game procurement plays, describing proven ways to resist discounting and protect margins, demonstrating ways to keep value at the forefront of negotiations, offering targeted tactics to protect hard-earned profits from mindless discounting, and detailing eight strategies effective in any type of pricing negotiation. This book will be an invaluable resource for B2B sales professionals, customer-facing professionals, and executives responsible for leading successful sales organizations.